APPLICATION AND RESEARCH OF ACOUSTIC EMISSION TECHNOLOGY IN DYNAMIC MONITORING OF WIND TOWER - ZHANG PengLin; LIU RuiJun; WEI XiaoHong; KONG Peng; DENG HuiQing (Jixie qiangdu)
For the hazards caused by crack to wind tower in service process,acoustic emission（ AE） technology was applied for extracting the characteristic signal of the crack. The attenuation test for AE signal of the wind tower and three-point bending test for the wind tower material Q345 E steel were carried out. At the same time,proportionality coefficient of different types of AE signal at the same frequency band was extracted by using the wavelet analysis method. It is demonstrated that the AE signal decayed obviously at the weld joint compared to parent metal,meanwhile the signal can reached farthest 6 m in wind tower. There was a relationship between the bending damage level of steel Q345 E and AE signal response characteristic. The energy ratio coefficient of different types of AE signals in the same frequency band was significantly different. It shows that the degree of safety of wind power tower in service can be estimated qualitatively according to the AE technology.